2000
DOI: 10.1177/088307380001500807
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers Classified as Having Attention-Deficit Hyperactivity Disorder (ADHD): DSM-IV Symptom Endorsement Pattern

Abstract: In the present study, 50 preschoolers were formally and independently classified using both the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) and third edition-revised (DSM-III-R) criteria for attention-deficit hyperactivity disorder (ADHD). The sample consisted of 25 preschoolers classified as having ADHD and 25 typically developing preschoolers for comparison; the sample was matched on gender, age, and socioeconomic status. All 50 preschoolers were without neurologic or neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
5
27
1
4
Order By: Relevance
“…15,16 The internal validity of the ICD-10 and DSM-IV models is also a focus of research and discussion. [17][18][19][20][21][22][23][24] Studies have been carried out, for example, to compare the impact of application across cultures and age groups. Issues of prevalence, co-morbidity and aetiology, related to internal validity, are highlighted below.…”
Section: Published In 2000 the Fourth Edition Of The Diagnostic And mentioning
confidence: 99%
“…15,16 The internal validity of the ICD-10 and DSM-IV models is also a focus of research and discussion. [17][18][19][20][21][22][23][24] Studies have been carried out, for example, to compare the impact of application across cultures and age groups. Issues of prevalence, co-morbidity and aetiology, related to internal validity, are highlighted below.…”
Section: Published In 2000 the Fourth Edition Of The Diagnostic And mentioning
confidence: 99%
“…Os pré-escolares com TDAH estão mais propensos a acidentes leves, mas não são mais suscetíveis a lesões graves 37 . Quando o diagnóstico de TDAH é estabelecido em pré-escolares usando-se os critérios do DSM-IV, tem-se observado que as manifestações de hiperatividade e impulsividade são mais proeminentes que aquelas relacionadas ao déficit de atenção 38 .…”
Section: Transtorno Do Déficit De Atenção/hiperatividadeunclassified
“…Authors such as Barkley 32 discuss whether the type with predominance of inattention (without hyperactivity) truly represents a subtype of ADHD. In the study by Byrne et al 33 with pre-school children, 68% of them showed hyperactive/impulsive ADHD type, 28% combined ADHD, and 4% had predominance of inattention using DSM-IV criteria. As for the sample of Montiel-Nava et al, 31 using the Conners Scale with students aged 6 to 12 years, in Venezuela, there was a 5.7% prevalence of combined ADHD,1.14% with predominance of attention deficit and only 0.35% with hyperactive/impulsive predominance.…”
Section: Discussionmentioning
confidence: 97%